Răspunsuri

Cel mai inteligent răspuns!
2014-05-27T22:43:29+03:00
(\vec{u}+\vec{v})^2=(\vec{u}+\vec{v})(\vec{u}+\vec{v})=\vec{u}\cdot\vec{u}+\vec{u}\cdot\vec{v}+\vec{v}\cdot\vec{u}+\vec{v}\cdot\vec{v}.

Dar \vec{u}\cdot\vec{v}=|u||v|\cos \alpha =\vec{v}\cdot\vec{u} .

Deci (\vec{u}+\vec{v})^2=\vec{u}\cdot\vec{u}+2\vec{u}\cdot\vec{v}+\vec{v}\cdot\vec{v}

În același timp, găsim identitățile:

\vec{u}\cdot\vec{u}=|u|\cdot |u|\cdot\cos0=|u|\cdot |u|=|u|^2 \\  \\ \vec{v}\cdot\vec{u}=|v|\cdot |v|\cdot\cos0=|v|\cdot |v|=|v|^2

În concluzie, (\vec{u}+\vec{v})^2=|u|^2+2\vec{u}\cdot\vec{v}+|v|^2
2 5 2